2020
DOI: 10.21037/apm-20-184
|View full text |Cite
|
Sign up to set email alerts
|

Current status of ex-vivo liver resection and autologous liver transplantation for end-stage hepatic alveolar echinococcosis

Abstract: Hepatic alveolar echinococcosis (HAE) is a cosmopolitan zoonosis distribute widely in the northern hemisphere with high estimated 10-year mortality. Radical resection combined with oral albendazole administration are the major methods for HAE treatment, whereas most patients delayed diagnosis and treatment because which was considered as benign disease. For the cases with end-stage HAE could not be treated through conventional hepatectomy, allograft liver transplantation (LT) was regarded as a life-saving tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
0
10
0
1
Order By: Relevance
“…Accumulating evidence has indicated that nerve cells, adipocytes, osteoblasts and stem cell transplantation therapy are conducive to tissue damage repair and functional recovery ( 32 34 ). HIRI is a common pathological event during liver surgery, and is widely accepted as a common and inevitable complication during liver resection and liver transplantation, particularly in patients with end-stage liver disease ( 35 ). Moreover, the commonly used treatment methods for this include liver resection and liver transplantation, and thus, a method to reduce the I/R injury of the liver during surgery will be of great significance to the clinical treatment of liver diseases ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that nerve cells, adipocytes, osteoblasts and stem cell transplantation therapy are conducive to tissue damage repair and functional recovery ( 32 34 ). HIRI is a common pathological event during liver surgery, and is widely accepted as a common and inevitable complication during liver resection and liver transplantation, particularly in patients with end-stage liver disease ( 35 ). Moreover, the commonly used treatment methods for this include liver resection and liver transplantation, and thus, a method to reduce the I/R injury of the liver during surgery will be of great significance to the clinical treatment of liver diseases ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of treatment for hepatic hydatid disease, surgery remains the primary approach for the treatment of hepatic AE; radical resection combined with oral albendazole/mebendazole administration is a common method of treating AE ( 19 ). However, most patients experience a delayed diagnosis, and liver transplantation has been necessary to cure some patients ( 20 , 21 ). In our patient, the liver cysts had already spread, and curative treatment could not be performed at the initial suspicion of echinococcosis; only the ascites could be treated.…”
Section: Discussionmentioning
confidence: 99%
“…In the anhepatic phase of this human operation, the native liver is completely removed from the abdominal cavity for treatment, an artificial vascular graft is applied to temporarily reconstruct the IVC, and a portocaval shunt is established ( Yang et al, 2018 ). The reported anhepatic phase in alveolar echinococcosis ranges from 104 to 879 min ( Aji et al, 2018 ; Yang et al, 2018 ; Yang et al, 2020 ). According to the anhepatic phase of human reality viewpoint and comparing it with the survival data of our study, our rBELs would be efficient for sustaining physical perfusion phase in the absence of visible clots if they are used for this purpose in the future.…”
Section: Clinical Relevance Of Revascularized Bioengineered Livers Datamentioning
confidence: 99%